Características epistemológicas das teses de política educacional no triênio 2010-2012 - Tonieto, Carina (2018)
The general objective of the research that originates this thesis is to analyze the epistemological characteristics of educational policy theses in thetriennium 2010-2012. The research problem that guides the whole process expresses itself in the following question: do the theses defended on post graduation programs in Education that offer PhD, in the triennium 2010-2012 and linked to the educational policy lines of research,present epistemological frailties (theoreticalmethodological), as pointed out in the literature and which are their implications for the academic field of Educational Policy? The theoretical framework adopted is anchored in the contributions of Blanché (1988), Hessen (1987), Greco (2008), Paviani (2013), Japiassú (1992) and Bombassaro (1992), to locate the discussion about the concept of epistemology and in the historical rationalism of Bachelard (1968; 1977; 1978; 1990; 1996) and in the critical rationalism of Popper (1975; 2004; 2008; 2013), taken in their critical dimension, for the discussion about the epistemological issues imbricated in the process of scientific knowledge production. The method used is the deductive-analytical, because it starts from the general premise that all scientific research obeys the epistemological criteria (theoreticalmethodological), that qualify them as such, to afterward identify in a specific sample (theses defended in the triennium 2010-2012) the presence or not of such criteria and to analyze which are the implications of it for the Educational Policy academic field. Referring to the methodology the research is of basic nature; by itsqualitative problem approach, its descriptiveanalytical goals; and its procedures that are meta-research (TELLO and MAINARDES, 2015). The procedure adopted for the composition of the sample, which counts with 27 theses, was the analysis of the Capes Indicators Notebooks (2010; 2011; 2012), using as criteria the link of works to the Educational Policy lines of research and the policy/ies educational/s and/or public terms in their titles. The data collection was made through the reading ofthe full theses, using the technique of content analysis (BARDIN, 2011). The data were systematized and organized into spreadsheets, treated by means of a simple percentage for the indication of index of representativeness and analyzed based on the theoretical rationalist historical-critical framework. The initial hypothesis – which was confirmed – was that the theses would present the epistemological (theoretical-methodological) frailties pointed out in the literature. The main conclusions of the study were: the Educational Policy theses defended in the triennium 2010-2012, present epistemological frailties for not articulating in a satisfactory way the theoretical and methodological elements, which is evidenced by the unclear enunciation of these elements in the theses texts, entailing a difficulty to overcome the epistemological-ideological obstacles and to put in action the epistemological vigilance;to consider only the abstract of dissertations and theses in research that seek to identify the epistemological characteristics of the academic production can lead to wrong conclusions, because most of the information appears in the textual elements of the theses. In this direction, a challenge to the Educational Policy academic field is placed, the formation of researchers and the fomentation to studies that discuss the epistemological questions in educational policy research.